Improving Early Childhood Social Interaction through Learning Models Technology Based - Andi Saputri, Halimah; Regina Putri, Andini; Ningsih, Lisa; Fitrah Andikos, Adi (CV Kalimasada Group, 2024)
This article discusses the importance of social interaction in early childhood and how technology-based learning models can improve social interaction. In today's digital era, the use of technology in education is becoming increasingly relevant, especially for children who are in a crucial phase of social development. This article identifies various technology-based learning methods, such as educational applications and online learning platforms, that can encourage collaboration and communication between children. Through this approach, children not only learn academic skills, but also social skills such as sharing, collaborating, and communicating effectively. This shows that the integration of technology in learning can create an interactive and engaging environment, thereby increasing children's motivation and participation in social activities. This article concludes that the application of technology-based learning models is an effective strategy to support the development of social interaction in early childhood, and provides recommendations for educators and parents in its implementation